PECULIARITIES OF APPLICATION OF SEISMOACOUSTIC LOCATION FOR DETERMINATION OF MOVING OBJECTS - Ільченко , В.В.; Нікіфоров , М.М.; Мостовой , В.С.; Попков , Б.О.; Лоза , В.М.; Кульський , О.Л. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2022)
The work is related to the study of surface waves in solving seismic acoustic location problems during the movement of moving objects, and in assessing the accuracy of determining the coordinates of moving objects of different origins. In solving the inverse problems of seismic acoustic location, the surfaces of the wave that occur on the Earth's surface during the movement of a moving object are studied. The accuracy of the solution of the inverse problem directly depends on the errors: determination of the time of entry of the seismic acoustic wave, the velocity characteristics of the environment, noise of various origins, the choice of the geometry of the location of sensors.The need to study surface waves, namely Rayleigh Waves and Lion Waves, is justified because they propagate on the Earth's surface. The plane of oscillation of Rayleigh waves is vertical to the Earth's surface and direction of propagation, and Lev waves have a horizontal plane of oscillation. As one of the considered problems of seismic acoustic location as a source of energy of a moving object, we take seismic energy, which occurs during human walking. Human walking is periodic. It excites impulses of displacement in the geological environment. According to the known coefficient of rigidity of the medium, it is possible to determine what will be the maximum deviation of the seismic receiver.The paper investigates surface waves, Rayleigh and Lev in solving seismic acoustic location problems during human movement, and identifies factors that affect the accuracy of determining the coordinates of a moving object. In terms of using surface waves to solve seismic location problems to identify moving objects, they have the following advantages: the energy of these waves does not disappear deep into the Earth, but propagates below its surface; their formation takes more than 60% of the energy of the source, and the formation of deep waves only 8%, such waves have much more energy;From this it can be concluded that even at low energies of the excitation source surface waves can be used to solve seismic location problems during the movement of moving objects and to assess the accuracy of determining the coordinates of these objects.

Робота пов'язана з дослідження поверхових хвиль в рішенні задач сейсмоакустичної локації під час переміщення рухомих об’єктів, та в оцінюванні точності визначення координат рухомих об’єктів різного походження. В розв'язанні зворотних задач сейсмоакустичної локації досліджуються поверхні хвилі, які виникають на поверхні Землі під час руху об’єкту що переміщується. Точність розв'язку оберненої задачі безпосередньо залежить від помилок це: визначення часу вступу сейсмічної акустичної хвилі, швидкісної характеристики середовища, шумів різного походження, вибору геометрії розстановки датчиків. Обґрунтована необхідність в дослідженні поверхневих хвиль, а саме Хвиль Релея і хвиль Лява, тому що вони поширюються по поверхні Землі. Площина коливань релеєвських хвиль вертикальна до поверхні Землі та напрямку поширення, а хвилі Лява мають горизонтальну площину коливань. В якості однієї з розглядаємих задача сейсмоакустичної локації за джерело енергії рухомого об’єкту ми приймаємо сейсмічну енергію, яка виникає під час крокування людини. Крокування людини є періодичним. Воно збуджує імпульси зміщення у геологічному середовищі. За відомим коефіцієнтом жорсткості середовища можна визначити, яким буде максимальне відхилення сейсмоприймача. В роботі досліджені поверхові хвилі, Релея та Лява в рішенні задач сейсмоакустичної локації під час переміщення людини, та визначені фактори що впливають на точності визначення координат рухомого об’єкту. З погляду використання поверхневих хвиль для вирішення задач сейсмоакустичної локації для визначення рухомих об’єктів вони мають такі переваги: енергія цих хвиль не зникає у глибині Землі, а поширюється під її поверхнею; на їх утворення йде більш ніж 60 % енергії джерела, а на утворення глибинних хвиль тільки 8 %, то такі хвилі мають набагато більшу енергію; З цього зроблено висновок, що навіть за незначних енергій джерела збудження поверхові хвилі можуть бути використані для рішення задач сейсмоакустичної локації під час переміщення рухомих об’єктів та в оцінюванні точності визначення координат цих об’єктів.
ОСОБЛИВОСТІ ЗАСТОСУВАННЯ СЕЙСМОАКУСТИЧНОЇ ЛОКАЦІЇ ДЛЯ ВИЗНАЧЕННЯ РУХОМИХ ОБ’ЄКТІВ
Keywords: surface waves; seismic location; moving object; seismic receiver; поверхові хвилі; сейсмоакустична локація; рухомий об’єкт; сейсмоприймач